Transient steel quality under non-isothermal conditions in a multi-strand billet caster tundish: part I. Analysis of fluid flow, thermal behaviour and inclusion behaviour. (3rd July 2017) - Chatterjee, S.; Chattopadhyay, K.
Abstract : A numerical model based on computational fluid dynamics was used to simulate the effect of non-isothermal conditions on melt flows in a multi-strand billet caster tundish. To start with, water was used as the operating fluid in a one-third scale tundish to calculate the fluid flow and temperature fields under isothermal and non-isothermal conditions. The model was then extended to the full-scale tundish with molten steel as the operating liquid in order to simulate the conditions in a real plant. It was observed that using step inputs of 10° and 23° for water and steel cases, respectively, changed the fluid flow patterns significantly, more so at locations far from the inlet, due to stronger buoyancy-driven natural convective flows. The temperature distribution and inclusion trajectories within the tundish were also affected due to the presence of non-isothermal conditions.